THE DEVELOPMENT OF METAPHOR AND SCIENTISTS OPINION ABOUT ITS EXISTENCE IN ARABIC AND AL-QURAN AL-KARIM / ØªØ·ÙˆØ± Ø§Ù„Ù…Ø¬Ø§Ø² ÙˆØ¢Ø±Ø§Ø¡ Ø§Ù„Ø¹Ù„Ù…Ø§Ø¡ Ø¹Ù† ÙˆØ¬ÙˆØ¯Ù‡ ÙÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆØ§Ù„Ù‚Ø±Ø¢Ù† Ø§Ù„ÙƒØ±ÙŠÙ… - Muhammad Danial Fahmi; Mohamad Yusuf Ahmad Hasyim (Lughawiyah: Journal of Arabic Education and Linguistics, 2023)
This study aims to determine the metaphor’s development and scientists opinion about its existence in Arabic and Al Quran. Studying metaphor in rhetoric discourse is important because it is related to Al Quran's stylistic and metaphor is a part of it. It is undeniable that metaphor evolved from the beginning of its emergence. Furthermore, experts argued on the existence of metaphor. The type of this research was literature review. The data in this research were obtained from relevant references. The results indicate that metaphor is part of language use. The first person to use metaphor was Abu Ubaidah Muammar Al Mutsanna. This term was developed by Al Jurjani who classified metaphor into majaz lughawi and majaz aqliy. Experts also argued on the existence of metaphor in Al Qur’an and Arabic. According to some of them, metaphor is not entirely included in the Qur’an.. Others claim that metaphor appears in the Qur'an and Arabic. Because the existence of metaphor is particularly significant in the meaning of language, the researcher choose the majority opinion that metaphor can be found in the Qur'an and Arabic.